Gambaran Faktor-Faktor Ibu Yang Tidak Memberikan Asi Eksklusif Di Desa Cepokosawit Kabupaten Boyolali - Kusumaningrum, Tiyas; , ArinaMaliya,S.Kep.M.Si.Med; , Dian Hudiyawati, S.Kep., Ns (2016)
Breast milk is a white liquid produced by the mammary gland mother through breastfeeding. Naturally he is able to produce breast milk. Breast milk is a food that has been prepared for the baby when she was on pregnanch. World Health Organization is giving only breast milk without giving other foods and drinks to babies from birth until the age of 6 month, except medicine and vitamins.but by no means exclusive breastfeeding after exclusive breasfeeding stopped, but still be given to the baby until the baby is two years old. To promote breast feeding early on required supporting factors are continuous for successful breastffeding, among other things depending on the role performed by health workers, hospital policy, and governments, mother, family,community, and the baby alone. The purpose of this study is to describe the factors mothers who do not provide exclusive breastfeeding in rural districs cepokosawit boyolali. Sampling technique using total with a sample 32 respondents with baby agen 0-6 months. Instrunents used in this study was a questionnaire data analysis techniques used by univariate analysis in the form of the frequency distribution. Research shows the average maternal age 20-25 is 18 respondents (56,3%), while those aged 26-30 are 14 respondents (43,7%) knowledge of mothers on average less about ASI as many as 16 respondents (50,0%) education is largely SD-SMP 15 respondents (46,9%), mothers to work an average of 12 respondents are private employees (37,5%) respondents low socioeconomic level as many as 16 (50,0%) for the support of her husband of less that 14 respondents arguing ation is not enough then the baby has not reached the age of 6 months has been given additional food. Keyword :mother,exclusive breastfeeding, breast feeding.